Histological and Histochemical Studies on Harderian Gland of the Pig (Sus scrofa) - Gahlot, Parveen Kumar (Indian Journal of Veterinary Anatomy, 2019)
The present study conducted on Harderian gland of five pigs of 5-6 months revealed that the gland was multilobulated tubulo-acinar covered with thick connective capsule. The glandular parenchyma was consisted of numerous acini with irregular lumen. The plasma cells and lymphocytes were located between the interstitialtissues of the gland. The lymphoid aggregates were observed in the parenchyma. The excretory duct system was observed to be very elaborative and extensive which comprised of intralobar and interlobar ducts. The histochemical studies showed a strong positive reaction for presence of glycogen, a predominantce of neutralmucosubstances and a minute amount of sialomucins and hyaluronic acid.